Analysis of Digital Optimization Strategy at Al Eiman Royal Hotel Madinah during Pandemic - Zulkifli Zulkifli; Redjeki Agoestyowati; Nila Prasetyningsih; Yuni Heriyanti; Endra Marsudi (Yayasan Ilomata, 2022)
This research aims to analyze digital optimization Al Eiman Royal hotel, to analyze decision-making efforts are to deal with problems that arise during the pandemic. It also to see the digital optimization strategy carried out by hotels in Madinah during the pandemic. Data analysis source by searching, collecting data by conducting observations and interviews and then making conclusions so that they are easy to understand. The interview technique that will be used is a structured interview. The various data obtained are then processed and analyzed using the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), TOWS Matrix, and IE Matrix to conclude the strategies that have been carried out and inputs that can be used by Al Eiman Royal Hotel as a reference for optimizing the implementation of digital strategies during the pandemic. According to the research result, the IFE and EFE matrix with a total weight of 3.45 for IFE and 2.51 for EFE puts the hotel is in a Growth Stability position with a strategy to keep and maintain the existing market while being able to develop with new types of services also can formulate strategic options for hotel directions using the TOWS matrix.